Innovative Revenue Models for Islamic Boarding Schools: Achieving Economic Autonomy - Hafidh, Zaini; Sururi, Sururi; Nurdin, Nurdin; Adinata, Ambar Radya; Ramadhan, Ryneva Anevia (Indonesian Research Journal in Education |IRJE|, 2024)
This research aims to analyze the concept of self-generated revenue in Islamic boarding schools to support their economic independence. This research employs a qualitative with a case study approach, using interviews, document studies, and observations for data collection, Focus Group Discussion to gather views and ideas from various stakeholders regarding innovative revenue models for Islamic boarding schools, validation, and triangulation, assisted by NVIVO software for data analysis. The research is conducted at the Ar-Risalah Islamic Boarding School in Ciamis Regency. The findings indicate that the Ar-Risalah Islamic Boarding School is currently running and developing businesses in agriculture, fisheries, mining, farming, and integrated waste management. The profits from these businesses promote the economic independence of the boarding school and have a wide impact not only on the school itself but also on the surrounding community involved in the boarding school’s businesses.